2013
DOI: 10.1590/s1413-35552012005000125
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder isokinetic profile of male handball players of the Brazilian National Team

Abstract: BackgroundData obtained on an isokinetic dynamometer are useful to characterize muscle status and have been reported in muscle imbalance studies in different types of sport. However, few studies have assessed elite handball players to establish reference values. ObjectiveThe purpose of this study was to compare, for the dominant (D) and non-dominant (ND) side, the isokinetic profile of shoulder rotator muscle strength between male handball players (H) and asymptomatic non-athletes (NA). MethodIsokinetic concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
1
28
3
3
Order By: Relevance
“…Our volunteers demonstrated lower strength values of knee flexor and extensor muscles than previous data of elite soccer players . Athletes of both sexes involved with FMHI, however, demonstrated higher shoulder strength values than those demonstrated by women wrestlers and by elite female athletes or male handball players .…”
Section: Discussioncontrasting
confidence: 68%
“…Our volunteers demonstrated lower strength values of knee flexor and extensor muscles than previous data of elite soccer players . Athletes of both sexes involved with FMHI, however, demonstrated higher shoulder strength values than those demonstrated by women wrestlers and by elite female athletes or male handball players .…”
Section: Discussioncontrasting
confidence: 68%
“…To assess muscular strength profile, isokinetic testing has been used by clinicians and physical therapists. 23,28,29 Several studies have been carried out to establish strength profiles in soccer players. [30][31][32] However, only one study has investigated isokinetic strength in futsal players 33 while none have been conducted in beach soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…Saccol et al measured the shoulder ER and IR PT at 60°/s and 180°/s angular velocities in elite child tennis players and found that this ratio changed between 68% and 96% (23). Considering other studies reported in the literature, the ER/IR ratio was reported as 65%-74% in cricket players (11), 72%-74% in male handball players (15), 78%-85% in professional swimmers (10), 66%-70% in adolescent handball players (16), 72%-78% in women volleyball players (8) 61%-64% in normal healthy male individuals, and 67%-69% in healthy women individuals (7). The present study found that the ER/IR was approximately 47%-67% for the dominant side at 60°/s in weightlifters, approximately 59%-77% for the nondominant side, approximately 37%-57% for the dominant side at 240°/s velocity, and approximately 33%-53% for the nondominant side.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, objective assessment of muscle strength in all athletes is crucial to the sportive success of athletes and prevention of injuries. Despite several studies in the literature exploring the upper extremity isokinetic strength profile in various sports fields such as swimming, handball, volleyball, tennis, water polo, cricket, judo, and basketball (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), no study has examined the upper extremity isokinetic muscle strength characteristic in weightlifters.…”
Section: Introductionmentioning
confidence: 99%